Implementation Of Poac Management (Planning, Organizing, Actuating And Controlling) In An Effort To Reduce The Number Of Pending Claims For Inpatient Bpjs In The Hospital - Tri Utami, Yeni; Maryati, Warsi; Sri Rahayuningsih, Lilik Anggar (LPPM Universitas Duta Bangsa Surakarta, 2024)
Problems with pending claims in hospitals are mostly caused by incomplete files and discrepancies in the accuracy of diagnosis codes. UNS Surakarta Hospital is known to find around 50-300 BPJS Inpatient claim files pending every month. This study aims to determine management in an effort to reduce the number of pending claims for inpatient BPJS patients in hospitals. This type of research is descriptive qualitative, with a cross sectional approach. The subjects of this research include claims coordinators, coders, internal verification officers and medical committee members (doctors). The research object is the claim file for Trimonths 4 of 2023. The instruments used are interview guidelines, observation guidelines, checklists. The research results showed that of the 2289 claim files submitted, 168 files (7.34%) were pending, which were divided into 3 factor classifications, namely Medical Aspects 62 files (36.90%), Administrative Aspects 57 files (33.93%) and Coding Aspect 49 files (29.17%). The process of handling pending claims based on planning, organizing, actuating and controlling aspects is still not running optimally. This is caused by the lack of clear division of job descriptions and the absence of SOPs related to handling pending claims which are only manifested in official notes, in general evaluations are still carried out based on cases but not based on users which causes there to be no rewards and punishments for officers who do not comply. It would be better for hospitals to prepare SOPs for filling out BPJS claim requirements files, and make clear job desk divisions, especially the BPJS coding section, and implement Inpatient RME immediately.